Antimicrobial peptide modification enhances the gene delivery and bactericidal efficiency of gold nanoparticles for accelerating diabetic wound healing. (6th September 2018) - Wang, Song; Yan, Chang; Zhang, Ximu; Shi, Dezhi; Chi, Luxiang; Luo, Gaoxing; Deng, Jun
Abstract : Impaired angiogenesis and bacterial infection have increasingly been implicated as the major causes of delayed diabetic wound healing. Abstract : Impaired angiogenesis and bacterial infection have increasingly been implicated as the major causes of delayed diabetic wound healing. However, there is currently no effective therapy. Here, we optimized a novel gene delivery system based on antimicrobial peptide (LL37) grafted ultra-small gold nanoparticles (AuNPs@LL37, ∼7 nm) for the topical treatment of diabetic wounds with or without bacterial infection. AuNPs@LL37 combines the advantages of cationic AuNPs that condense DNA with those of antibacterial peptides, which are both highly antibacterial and essential for enhancing cellular and nucleus entry to achieve high gene delivery efficiency. AuNPs@LL37 combined with pro-angiogenic (VEGF) plasmids (AuNPs@LL37/pDNAs) significantly improved the gene transfection efficiency in keratinocytes compared with pristine AuNPs/pDNAs, and showed similar expression to Lipo2000/pDNAs (a well-known highly efficient gene transfection agent). Moreover, our therapeutic depot showed higher antibacterial ability than the free antimicrobial peptides and the cationic AuNPs alone in vitro and in vivo due to synergistic effects. Furthermore, the combined system promoted angiogenesis and inhibited bacterial infection in diabetic wounds, resulting in accelerated wound closure rates, faster re-epithelization, improved granulation tissue formation and high VEGF expression. Finally, our therapeutic depot was highly biocompatible in vitro and in vivo, suggesting its potential as a feasible way to treat chronic diabetic wounds.